Intention to Use Social Networking Sites Among Malaysian Chinese Older Adults - Ooi, Chia Sin; Siah, Poh Chua; Low, Sew Kim (UI Scholars Hub, 2020)
Research has shown that social networking sites (SNS), such as Facebook and WhatsApp, make it more convenient for older adults to bond with friends and family. However, despite such benefits, studies also found few older adults use SNS, and even fewer older adults use SNS in less developed nations. Therefore, it is important to identify factors that can influence intention to use SNS in older adults, especially among the Malaysian Chinese population, as they will face an aging society earlier than other ethnic groups in Malaysia. This study used the Technology Acceptance Model and Reasoned Action Approach to examine whether factors such as perceived ease of use, perceived usefulness, selfefficacy, and subjective norms, are significant predictors of intention to use SNS among Malaysian Chinese older adults. Purposive and snowball sampling methods were used to recruit 288 Malaysian Chinese adults aged 60 and above to participate in this survey. Multiple regression was used to analyze the data. Results showed that subjective norms played the most important role in intention to use SNS among Malaysian Chinese older adults. These findings can provide insight for program managers and policymakers when promoting SNS use among older adults.